Digital questionnaire platform in the Danish Blood Donor Study. Issue 135 (October 2016) - Burgdorf, K.S.; Felsted, N.; Mikkelsen, S.; Nielsen, M.H.; Thørner, L.W.; Pedersen, O.B.; Sørensen, E.; Nielsen, K.R.; Bruun, M.T.; Werge, T.; Erikstrup, C.; Hansen, T.; et al.
Highlights: The Danish Blood Donor Study was established in 2010 and by the fall of 2015, 100, 000 Danish blood donors had been included. At inclusion, plasma and blood for DNA analyses are collected and saved in the biobank and all participating donors have completed a four-page paper-based questionnaire on health related issues. To be more cost-effective, we have developed and implemented a digital tablet-based questionnaire platform, using the open source survey software tool LimeSurvey. Here we describe the details of methods for the platform which enables a faster and more flexible procedure to collect valid questionnaire data from participating donors. The overall system can be used around the world by the use of internet connection, but the level of security depends on the sensitivity of the data to be collected. Abstract: Objectives: The Danish Blood Donor Study (DBDS) is a prospective, population-based study and biobank. Since 2010, 100, 000 Danish blood donors have been included in the study. Prior to July 2015 all participating donors had to complete a paper-based questionnaire. Here we describe the establishment of a digital tablet-based questionnaire platform implemented in blood bank sites across Denmark. Methods: The digital questionnaire was developed using the open source survey software tool LimeSurvey. The participants accesses the questionnaire online with a standard SSL encrypted HTTP connection using their personal civil registration numbers. The questionnaire is placed at a front-end web server and a collection server retrieves the completed questionnaires. Data from blood samples, register data, genetic data and verification of signed informed consent are then transferred to and merged with the questionnaire data in the DBDS database. Results: The digital platform enables personalized questionnaires, presenting only questions relevant to the specific donor by hiding unneeded follow-up questions on screening question results. New versions of questionnaires are immediately available at all blood collection facilities when new projects are initiated. Conclusion: The digital platform is a faster, cost-effective and more flexible solution to collect valid data from participating donors compared to paper-based questionnaires. The overall system can be used around the world by the use of Internet connection, but the level of security depends on the sensitivity of the data to be collected.